(untitled) - Lappé, Frances Moore (San Francisco, 2006)
There is a small number of people in every generation who are forerunners in thought, action, spirit, who swerve past the barriers of greed and power to hold a torch high for the rest of us. Frances Moore Lappé is one of those. Her writing has done that again and again. Here, in her latest work, she brings the familiar eloquency of expression, simplicity of language, poetic and passionate, to our nation’s most urgent problem, the reclaiming of democracy
Keywords: Democracy,Political participation,United States,Chế đô dân chủ; Politics and government; 1989-; United States,United States,Hoa Kỳ